Designing reading tasks using authentic materials as supplementary reading materials for the teaching of reading skill on ESP program to the second year nurse students at Nam Dinh University of Nursing - Lê, Thị Hương Giang (ĐHNN, 2017)
Chapter 1: Introduction. Chapter 2: Literature Review. Chapter 3: Designing reading tasks using authentic materials as supplementary reading materials for the teaching of reading skills for 2nd – year nurse students at NDU. Chapter 3: Conclusion.